Survival of Patients Subjected to Hepatectomy After Spontaneous Rupture of Hepatocellular Carcinoma: A Meta-analysis of High-quality Propensity Score Matching Studies - Huang, Xiaozhun; Jia, Chenyang; Xu, Lin; Bi, Xinyu; Lai, Fengyong; Huang, Zhangkan; Li, Xiaoqing; Yin, Xin; Ni, Yong; Che, Xu (Frontiers in Oncology, 2022)
Background: The spontaneous rupture of hepatocellular carcinoma (HCC) is associated with high mortality rates, and liver resection can provide better outcomes than other available treatments. However, the survival length of patients subjected to hepatectomy after spontaneous rupture of hepatocellular carcinoma remains controversial. Method: Articles reporting the comparison of the survival outcome between patients with rupture HCC (rHCC) and non-rupture HCC (nrHCC) from the inception until December 31, 2021 by PubMed, Web of Science, OVID, and the Cochrane Library databases were included. The high-quality propensity score matching analysis was used to investigate the impact of rupture on disease-free survival (DFS) and overall survival (OS) between the rHCC and nrHCC group with no heterogeneity. Result: A total of 606 patients from six cohort studies were included. The major baseline characteristics of the eligible patients were well balanced between rHCC and nrHCC group. The 1-, 3-, and 5-year hazard ratios of DFS were 3.45 (95% confidence interval [CI] 2.54–4.68), 3.63 (95% CI 2.87–4.60), and 3.72 (95% CI 2.93–4.72), respectively. The 1-, 3-, and 5-year hazard ratios of OS were 5.01 (95% CI 3.26–7.69), 5.49 (95% CI 4.08–7.39), and 4.20 (95% CI 3.20–5.51), respectively. Conclusion: The present meta-analysis demonstrated that the DSF and OS were significantly shorter in the rHCC group than in the nrHCC group, thus revealing that spontaneous HCC rupture was a predictor of poor survival.